Malondialdehyde in Exhaled Breath Condensate as a Marker of Oxidative Stress in Different Pulmonary Diseases. (16th June 2011) - Bartoli, M. L.; Novelli, F.; Costa, F.; Malagrinò, L.; Melosini, L.; Bacci, E.; Cianchetti, S.; Dente, F. L.; Di Franco, A.; Vagaggini, B.; Paggiaro, P. L.
Abstract : Background . Oxidative stress plays a role in the pathogenesis of many chronic inflammatory lung diseases. Exhaled breath condensate (EBC) collection is a noninvasive method to investigate pulmonary oxidative stress biomarkers such as malondialdehyde (MDA). Subjects and Methods . We measured MDA levels in EBC in a large number of patients (N = 194 ) with respiratory diseases: asthma (N = 64 ), bronchiectasis (BE, N = 19 ), chronic obstructive pulmonary disease (COPD, N = 73 ), idiopathic pulmonary fibrosis (IPF, N = 38 ). Fourteen healthy nonsmoking subjects were included as controls. Results . Excluding IPF subjects, MDA levels were significantly higher in all disease groups than in control group. MDA was significantly higher in COPD than asthmatic and BE subjects. Among asthmatics, corticosteroids-treated subjects had lower MDA levels than untreated subjects. COPD subjects showed an inverse correlation between MDA concentrations and FEV1 % (rho: − 0.24, P < .05 ). Conclusions . EBC-MDA is increased in subjects with chronic airway disorders, particularly in COPD, and it is related to FEV1 reduction.